PERAN KEPERAWATAN GIGI DALAM MILLENNIUM DEVELOPMENT GOALS - I Gede Surya Kencana (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
In 2000 the Government of Indonesia together member states of the United Nations (UN) attended the Millennium Summit in New York and signed the Millennium Development Goals (MDGs), which has eight important goals. Efforts to realize the achievement of these goals is a challenge in development around the world, including health development. The role of dental nursing in accordance with the objectives of the MDGs are 1) eradicate extreme poverty and hunger, 2) Achieve universal primary education, 3) Promote gender equality and empower women, 4) Reduce child mortality, 5 Improve maternal health, 6) Combat HIV and AIDS, malaria and other diseases, 7) Ensure environmental sustainability 8)Develop a global partnership for development. Of the eight MDGs, it can be concluded that dental nursing has a role in achieving the goals and the MDGs.